Navigating the complexity of Wilms tumors in pediatrics: diagnostic challenges for better treatment - Mariana Andozia Morini; Isabela Werneck da Cunha (BMC, 2024)
Abstract Most pediatric kidney tumors clinically present as an abdominal mass, typically detected by the child's caregivers and later confirmed through imaging tests. Malignant renal cancers account for approximately 5% of childhood kidney neoplasms, with Wilms tumors (WT) being the most common diagnosis in this category (90% of cases). Patients are treated according to two main protocols: the American protocol of the Children's Oncology Group (COG) or the protocol from the Société Internationale d'Oncologie Pédiatrique (SIOP), which differ in terms of the timing of surgery (before or after chemotherapy). Grossly, pediatric kidney tumors are neoplasms that can vary significantly in size. After a correct histological diagnosis, the child will be treated according to the guidelines for that specific neoplasm. Therefore, the accurate diagnosis of the histological subtype is crucial for determining the appropriate treatment that can improve survival rates in children. Consequently, it is extremely important to recognize neoplasms that require differentiation from WT.